PENGARUH PERTUMBUHAN KREDIT PERBANKAN DAN PERTUMBUHAN JUMLAH ORANG BEKERJA TERHADAP PERTUMBUHAN EKONOMI PROVINSI RIAU - Aprian Doni Faizal; Syapsan Syapsan; Any Widayatsari (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This study aims to test and analyze empirically the effect of bank credit growth andthe number of people working on economic growth in Riau Province. This study us abanking credit growth, number of people growth and economic growth. The dataanalysis method used is multiple linear regression analysis with the help of theSoftware Statistical Package for Social Science (SPSS) program. The resultsshowed that the growth of bank credit and the number of people working had apositive and significant effect on economic growth in Riau Province. The contributionof the independent variable is the growth of bank credit and the number of peopleworking in explaining the dependent variable, namely economic growth of 58.6 %,the remaining 41,4 % is influenced by other variables not examined in this study.